From Natural Science didactics to popular education in Natural Sciences, environment and health. Reflections on a path to success (Praxis Educativa, 2012)
We present this paper, which is the result of reflections on the path taken by our working group, which we believe could also provide assistance to other groups interested in taking similar paths. This review has allowed us to identify a route which, having its beginnings in the field of Science Education, has taken us into areas we considered, in the first instance, to be represented by Popular Education in Natural Science, Environment and Health. We also share those experiences in research and teaching that have en-abled us to follow our particular theoretical and methodological course of action. These experiences involve diverse people with whom we put forth each of the ideas and proposals implemented and who also think, create, learn, decide and carry out the shared decisions. Our account is just one among many possible stories.
Keywords: Didactics; Popular Education; Natural Sciences; Environment; Health